Perancangan Sistem Informasi Pendaftaran Pasien Rawat Jalan Berbasis Web Menggunakan Metode Waterfall Pada Klinik Pratama Yakrija - Arif Cahyo Utomo; Kecitaan Harefa (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
At the Yakrija Pratama Clinic, it was found that patients who came had to register directly and in the data written in the patient registration book. The data collection process by writing the patient's identity by the registration officer is carried out one by one resulting in a queue. In addition, written data collection can slow down the performance of registration officers because they have to look for one by one processing the patient's medical record data that has been collected previously. Data storage in the form of documents also has the potential for data to be lost, tucked away or vulnerable to damage. And of course data collection in writing in the patient registration book resulted in making reports take quite a long time. From the problems above, the author makes a web-based outpatient registration information system application using the waterfall method as a system development method. This system is designed using the PHP and MYSQL programming languages ​​as database servers.